Espalhamento de ondas planas em esferas com rugosidade - Cesar, Silas Lenz (1989)
We study the scattering of a plane wave from a rough surface by using a perturbation expansion on the Mie theory and the results are valid for any wavelength. The rough is described in terms of the mean-square departure of the surface ( δrms ) from a perfect sphere and a Gaussian correlation with angular correlation length a . The scattered fields are obtained such that diferentiai cross section and the scattering matrix are calculated up to the second-order in δrms . The results are analized in the limit of long wavelength ( Rayleigh scattering ) as a function of the angular correlation length.